KONTROL PROSES PEMBELAJARAN PADA SISWA SMP TAMAN SISWA SAWIT SEBRANG KAB. LANGKAT - Ance Lumbantobing, Panni; Sidebang, Restio; Dewi, Sri; Hasratuddin (Universitas Negeri Medan, 2025)
Abstract: Academic achievement refers to the performance of students' learning outcomes after a period of learning knowledge and skills. Under the current education system, schools often express students' academic performance in the form of exams. An important factor in the control of the learning process is the student's ability factor in the learning process with the support of control is the role of parents, teachers and peers. The data of this study used Multivariate analysis. Because in this study it is more suitable for processing multi-layer structure data, decomposing the original single random error into the appropriate level, which can greatly improve the effect of fitting the model. In this study, the results obtained are by looking at the results of the Multivariate test, the results obtained are the role of process control of the three elements is with the support of family, the role of teachers and peers, the results are that the three variables greatly support the role of control of the learning process. Keyword: process control, multivariat, student ability Abstrak: Prestasi akademik mengacu pada kinerja hasil belajar siswa setelah periode pembelajaran pengetahuan dan keterampilan. Di bawah sistem pendidikan saat ini, sekolah sering kali mengungkapkan kinerja akademik siswa dalam bentuk ujian. Faktor penting dalam kontorl proses pembelajaran adalah faktor kemampuan siswa dalam proses pembelajaran dengan pendukung control adalah peran orang tua, guru dan teman sebaya. Data penelitian ini menggunakan analisas Multivariat. Karena pada penelitian ini lebih cocok untuk memproses data struktur multi-lapis, menguraikan kesalahan acak tunggal asli ke level yang sesuai, yang dapat sangat meningkatkan efek pemasangan model Dalam penelitian ini hasi lyang di dapat adalah dengan melihat hasil uji Multivariat makan hasil yang di dapat adalah peran control proses dari ketiga elemen adalah dengan dukungan keluarga, peran guru dan teman sebaya maka hasilnya adalah ketiga variable tersebut sangat mendukung peran control proses pembelajaran. Kata Kunci: kontrol proses, multivariat, kemampuan siswa